EFL LEARNERS’ PERCEPTIONS ON THE USE OF IDIOMS IN DAILY CONVERSATION (RETAIN, 2020)
There are many EFL learners think that idioms are very difficult to understand both from speaking and writing due to caused by several factors namely: the lack of new vocabulary, different cultural backgrounds and strategies which are being faced by EFL leaners. In general idioms look easy to learn or understand. However, this is not the case. An idiom is a combination of words whose meanings are integrated and cannot be interpreted directly, but can be interpreted together with sentences. Lazar (1996) states that figurative language is an area often neglected in the teaching of vocabulary. This study refers to EFL learners’ perceptions on idioms usage in daily use which makes learners difficult in understanding and using an idiom. Quantitative research was used in the process of collecting data and asking EFL learners to answer the questionnaires to identify their perception toward the usage of idioms in terms of speaking in their daily life. The subject was chosen among 35 EFL learners of ESC in English department from State University of Surabaya. Findings of this research are classified into two terms those are the idioms usage in manner and hardship. Manner refers to how EFL learners percieved their strategy in comprehending idioms in daily usage. While hardship refers to how EFL learner’s challenges in comprehending idiomatic expressions. Based on the result, EFL learners’ perceptions of idioms usage in daily conversation that most of the students have no strategy, have never practiced idioms in speaking and have difficulty, they consider that the idioms are difficult to apply in daily conversation. Meanwhile, some of them have their own strategies in overcoming difficulties and applying idioms in daily use. Their strategies are learning through social media, poetry, novels, films and google translation. The researcher suggests that EFL learner need to learn about idioms deeply regarding to the influence and importance of the idioms daily usage in conversation. Key words: Idioms, EFL learners, Perceptions, Strategies